TAX EVASION AND ITS IMPACT ON THE IRP FISCAL COLLECTION - Stefany Benítez Ruiz Díaz, Dora; Ysabel Benítez Ruiz Díaz, Jessica; Marlene Argüello Acosta, Liz; Areco, Juan; Dilda Quintana, Gladys (Revista Gênero e Interdisciplinaridade, 2023)
The IRP collected little in these first years of application. But, its main function in the tax system is not in collection, but in the formalization of the economy and the closing of the circle of tax control, which will promote equal opportunities in the market and increase the collection of other taxes. since evasion produces losses for the State and tax inequality, since “some pay more than others; It is not just a cash issue but an equity issue. The investigation develops the details of this tax regime because there is priority in the acquisition of knowledge and training of accountants and taxpayers in order to avoid tax evasion. The objectives of this work are to analyze the tax evasion of Personal Income Tax (IRP) – Income and Capital Gains (RGC) taxpayers and its impact on the country’s tax collection. The research design is descriptive. The survey was used as a data collection technique. The selected sample was 30 accountants and 30 taxpayers from Ciudad del Este. The type of sampling was probabilistic since the entire population had the same possibility of being surveyed. The results obtained demonstrated that tax evasion does exist, whether voluntary or involuntary, because there is no tax awareness; To achieve a fairer tax system, we must fight against evasion and avoidance: strengthening our legal framework to avoid tax maneuvers, improving oversight and effectively sanctioning offenders.